Penilaian semula konsep 'hegemoni' dalam kerangka hubungan antarabangsa - Awang, Saadon (2016)
A concept of international relations explains relations amongst countries in various fields, including political, economical, social, and law. Various aspects related to those fields had changed in term of perspectives, and redefinitions of some concepts are desperately required. The same reevaluation is required within the discipline of international relations. The development of international relations discipline had brought up another perspective of power, academically known as `hegemony’. The term hegemony refers to some degree of one’s ability to take control over others, physically or psychologically. The ability enables one who holds power to act as he intends, beyond others’ power and scope of laws they have.This paper discusses the concept of hegemony, the parties in possession of the ability, and some consequences from the acts in relation to the use of the ability within the framework of international relations today.